Biobanking Scheme for Forest Conservation in Peninsular Malaysia: A Brief Appraisal - Izawati Wook; Adzidah Yaakob; Dina Imam Supaat (USIM Press, 2024)
Malaysian Journal of Syariah and Law, Volume 10 Issue 1 Page (34-40)